MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMP NEGERI 3 BANGUNTAPAN - Balu, Hidayanti; Nur Sofiana, Arina; Subiyantoro (re-JIEM (Research Journal of Islamic Education Management), 2025)
School-Based Management (SBM) at SMP Negeri 3 Banguntapan features innovations and improvements in learning quality centered on students' needs.This study examines the implementation of School-Based Management (SBM) at SMP Negeri 3 Banguntapan in improving the quality of learning.This study employs a descriptive qualitative method involving the principal, teachers, students, and the school committee as research subjects.The research results indicate that SBM provides schools with autonomy to manage resources, curriculum, facilities, and funding effectively and efficiently.This implementation enhances teacher competencies, enriches teaching methods, and fosters an adaptive and inclusive learning environment.In addition, the integration of local cultural values into the curriculum strengthens students' identity and fosters collaborative relationships between the school and the community.However, there are several challenges, such as a lack of understanding of the SBM concept, limited human resources, and low community participation.For optimal success, support from the government, further training, and active collaboration from all stakeholders are necessary.This study affirms that SBM has great potential to improve the quality of education through participatory and innovative management.